PERSONALITY FEATURES OF CONVICTS WITH ADDICTIVE BEHAVIOR - Ganishina, Irina; Aksenova, Galina; Aksenova, Polina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the recent years the significant increase in number of convicts with addictive behavior is observed in correctional establishments of the Russian Federation. Addictive behavior is often caused by anomalies of the identity of convicts and is expressed in escape from reality by change of their mental state by means of use of narcotic and psychotropic substances, alcohol, game addiction, sexual addictions that is followed by intensive emotions development. Nowadays the modern society requires that correctional establishments of the penal system of Russia should become social clinics which are carrying out psychosocial rehabilitation of convicts with addictive behavior. The purpose of this research is studying psychological features of convicts with addictive behavior. The methods and techniques of the research are observation, conversation, analysis of personal records, expert poll, psycho-diagnostic testing (the test of addictive indicators of MGAA, K. Leonhard – H. Shmishek's test, L.N. Sobchik's technique "The individual and typological questionnaire", the LSI test of Kellerman-Plutchik-Konte), methods of mathematical statistics. It is defined that convicts with addictive behavior are conflictive, quick-tempered, insincere, show high levels on the scale of addictive indicators, have high indicators of exaltation, demonstrativeness and excitability. They have dominating conflict emotional states which are followed by high introversion and psychological protection as denial, rationalization, cognitive mapping. Such personal profile of convicts with addictive behavior testifies to the aggressive manner of self-affirmation contrary to the interests of people around, the increased suspiciousness and vigilance in the relations, high proneness to conflict. We consider that psychological features of convicts with addictive behavior are the indicator of success of their psychosocial rehabilitation.